Turbans vs. Helmets: A Systematic Narrative Review of the Literature on Head Injuries and Impact Loci of Cranial Trauma in Several Recreational Outdoor Sports - Dirk H. R. Spennemann (MDPI AG, 2021)
When in public, faith-based mandates require practising Sikh men to wear a turban which may not be covered by hats or caps. This makes it impossible for practising Sikhs to wear helmets and other protective headwear, mandatory in many countries and facilities for engagement in recreational pursuits (e.g., skiing) and on adventure outdoor recreation camps mandatorily run for school groups. The result is often social exclusion and ostracisation in the case of school children. Despite studies into the efficacy of protective helmets in some recreational outdoor activity settings, virtually nothing is known about the protective potential of turbans. This paper systematically reviews the extant literature on head injuries in several recreational outdoor activities and sports sectors (aerial, water, winter, wheeled and animal-based sports) and finds that the extant literature is of limited value when trying to understand the spatial distribution of trauma on the cranial surface. As the data do not permit to make inferences on the protective potential of turbans, future systematic, evidence-based epidemiological studies derived from hospital admissions and forensic examinations are required. Failure to do so perpetuates social exclusion and discrimination of religious grounds without an evidentiary basis for defensible public health measures.